2008
DOI: 10.1534/genetics.108.089458
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Redundant Isoforms of a Yeast Hsp70 Chaperone Subfamily Have Different Antiprion Effects

Abstract: ABSTRACT] strongly but in a manner distinct from Ssa1-21p, highlighting functional differences between these nearly identical Hsp70's. Our data uncover exquisite functional differences among isoforms of a highly homologous cytosolic Hsp70 subfamily and point to a possibility that variations in Hsp70 function that might improve fitness under optimal conditions are also important during stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 50 publications
(47 reference statements)
3
84
0
Order By: Relevance
“…Previously, we and others showed that [URE3] propagation is inhibited by increasing Ssa1p or depleting Ssa2p, but not by increasing Ssa2p or depleting Ssa1p (16)(17)(18)(19). We assessed functions of purified Ssa1p and Ssa2p in vitro to determine whether these differences might be due to differences in their biochemical activities.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previously, we and others showed that [URE3] propagation is inhibited by increasing Ssa1p or depleting Ssa2p, but not by increasing Ssa2p or depleting Ssa1p (16)(17)(18)(19). We assessed functions of purified Ssa1p and Ssa2p in vitro to determine whether these differences might be due to differences in their biochemical activities.…”
Section: Resultsmentioning
confidence: 97%
“…Growth of strain 1161, which lacks all four chromosomal SSA family genes (SSA1-SSA4), is supported equally well by Ssa1p or Ssa2p expressed from a plasmid (17), indicating that all essential Hsp70 functions of Ssa1p and Ssa2p are completely interchangeable. However, whereas [URE3] propagates stably in cells expressing only Ssa2p, it is unstable in cells expressing only Ssa1p (17).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations